Innovative Action of Halal Cryptocurrency Management Halal Cryptocurrency and Financial Stability - Nur Fauziyah; Azzam Shidqie (Majapahit Journal of Islamic Finance and Management, 2026)
In the Industry 4.0 era, the sudden growth of financial technologies, especially cryptocurrencies, has revolutionized financial transactions across the globe by providing decentralized, transparent, and efficient platforms. However, these new technologies have complex implications for existing legal and ethical standards, including Islamic law. The existing Shari'ah rules on cryptocurrencies are mostly responsive and disjointed, leaving the increasing number of Muslims, especially the younger generation, vulnerable to legal ambiguities and potential conflicts with the values of Islamic law. The volatility, speculation, and intangible nature of cryptocurrencies raise fundamental questions about their compatibility with Shari'ah values of banning riba, gharar, and maisir, while promoting values of justice, prudence, and transparency. This research work suggests an original halal cryptocurrency governance framework that is compatible with Shari'ah goals, covering product development, governance, risk management, and transaction mechanisms, thus integrating ethical Islamic values with financial technological innovation. By closing the gap between technological innovation and Shari'ah compliance, this framework is expected to promote a more inclusive, stable, and sustainable Islamic digital financial environment.